Nevus of Ota with palatal involvement: a case report - Derache Anaïs; Simon Etienne; Brix Muriel (EDP Sciences, 2023)
Nevus of Ota is a macular discoloration of the face which is most commonly found in the Japanese and females are more commonly affected than males. It is first described by Ota and Tanino in 1939, involves the skin along the distribution of first and second division of trigeminal nerve. Involvement of the palatal mucosa occurs rarely in nevus of Ota, it usually blends with the oral mucosa and is typically irregular, undefined and often present as a mottled patch. We describe here the case of nevus of Ota with palatal involvement in a 13-year-old Asiatic boy. His past medical history revealed the presence of the lesion since birth. There were no other pigmented lesion locations. The exact etiology of nevus of Ota is still unknown but they have the potential to undergo melanomatous change.